Linguistic Deviations: Characteristic of Online Language - Alma H. Ramadhani (Deskripsi Bahasa, 2019)
This study presents the analysis of a small corpus of online language taken from microblog site Instagram, examining the language characteristic focusing on the linguistic deviations. As a representation of CMC, Instagram allows its user to do a free communication with another users talking about personal experience or discussing anything that matches their interest without any limitation of characters. The data used in this research was in the form of words, phrases, clauses and fragments taken from Instagram Posts’ comments. The result shows that linguistic deviations found in Instagram are non-standard capital letters, over-used of punctuations, emoji, repeating characters, laughter, abbreviations, and grammatical deviation. Online language is believed to be creative and unique and those linguistic features indicate that online language on is a combination between written and spoken communication and it has opened avenues of online language that is not accessible with “correct English”.